Monitoring Iron Overload: Relationship between R2* Relaxometry of the Liver and Serum Ferritin under Different Therapies - Plaikner, Michaela (J Clin Imaging Sci, 2018)
OBJECTIVE: The objective of this study was to evaluate the relationship between hepatic magnetic resonance imaging (MRI) with R2* relaxometry and serum ferritin in therapy monitoring of patients with iron overload. Further, a possible influence of the chosen therapy (phlebotomy or chelation) was assessed. MATERIALS AND METHODS: We retrospectively evaluated 42 patients with baseline and follow-up R2* relaxometry and determination of serum ferritin before and during therapeutic phlebotomy or iron chelation therapy or watchful waiting, respectively. Linear regression analysis was used to analyze the correlation between changes of R2* and serum ferritin. Regression lines for different groups were compared with analysis of covariance. RESULTS: We found a moderate positive statistical correlation (r = 0.509) between serum ferritin and R2*, a moderate positive correlation between absolute R2* changes and serum ferritin changes (r = 0.497), and a strong correlation for percentage changes (r = 0.712). The correlation analysis between relative changes of R2* and serum ferritin for the different therapies resulted in a strong correlation between phlebotomy and chelation (r = 0.855/0.727) and a moderate for no applied therapy (r = 0.536). In 22/92 paired examinations, a discordance of R2* and ferritin was found, particularly involving patients under chelation. CONCLUSIONS: Despite the good correlation between serum ferritin and R2* relaxometry in monitoring iron overload, treatment response may be misinterpreted when only serum ferritin is considered. Although ferritin is an acceptable and far cheaper tool for monitoring, MRI should be performed for confirmation, especially in case of unexpected ferritin changes, particularly under chelation therapy.